Inventory Management System With Two-Factor Authentication For Heng Huat Motor & Electrical Trading - CHIA, JING YAN; HARUN, NUR ZIADAH (Applied Information Technology And Computer Science, 2025)
Inventory management system for Heng Huat Motor & Electrical Trading is a system designed to modernize and enhance its inventory control process. Since the current manual system lacks of inadequate security measures for safeguarding inventory data, it potentially leads to data loss and unauthorized access. With limited access control, the data are easily susceptible to potential breaches of confidentiality. By converting from manual paper records to a digital system, this system simplifies inventory management and promotes efficient restocking practices. A secure inventory management system is crucial to ensure secure inventory management and streamline the inventory management process. The comprehensive view of the product inventory and the timely stock alerts effectively prevent understocking issue. The product restocking and checkout process with barcode scanning ensures accuracy in calculating inventory levels. To secure the system, role-based access control and two-factor authentication are implemented to restrict unauthorized access. Strong passwords and time-based one-time passwords add an extra layer of security. Each user has different access based on their role within the company to safeguard the sensitive information. An agile model is used to develop the system since it is flexible and adaptable. This web-based system is mainly written in PHP programming language and all data are stored in MySQL. In short, this inventory management system with two-factor authentication helps Heng Huat to manage its effectively.